2012
DOI: 10.1186/1742-2094-9-215
|View full text |Cite
|
Sign up to set email alerts
|

Cellular sources of dysregulated cytokines in relapsing-remitting multiple sclerosis

Abstract: BackgroundNumerous cytokines are implicated in the immunopathogenesis of multiple sclerosis (MS), but studies are often limited to whole blood (WB) or peripheral blood mononuclear cells (PBMCs), thereby omitting important information about the cellular origin of the cytokines. Knowledge about the relation between blood and cerebrospinal fluid (CSF) cell expression of cytokines and the cellular source of CSF cytokines is even more scarce.MethodsWe studied gene expression of a broad panel of cytokines in WB from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 45 publications
6
45
0
1
Order By: Relevance
“…Both IL-6 and IL-1α have been implicated in the pathogenesis of neuroinflammation in MS [5,31,32,33], and, in accordance with our results, associated with early MS. On the other hand, we found that the expression of IL-10, a potent anti-inflammatory cytokine, was lower in PBMCs of MS patients, concordant with several studies of neuroinflammatory disorders [5,15,33]. IL-10 could be induced by type I IFN in monocytes, macrophages and CD4+ T lymphocytes [19], and represents an important negative feedback mechanism to downregulate uncontrolled production of proinflammatory cytokines (IL-1β, IL-6, IL-17, TNF-α), protecting brain homeostasis [5,16,33]. …”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Both IL-6 and IL-1α have been implicated in the pathogenesis of neuroinflammation in MS [5,31,32,33], and, in accordance with our results, associated with early MS. On the other hand, we found that the expression of IL-10, a potent anti-inflammatory cytokine, was lower in PBMCs of MS patients, concordant with several studies of neuroinflammatory disorders [5,15,33]. IL-10 could be induced by type I IFN in monocytes, macrophages and CD4+ T lymphocytes [19], and represents an important negative feedback mechanism to downregulate uncontrolled production of proinflammatory cytokines (IL-1β, IL-6, IL-17, TNF-α), protecting brain homeostasis [5,16,33]. …”
Section: Discussionsupporting
confidence: 53%
“…Using cultured synovial fibroblasts and macrophages, it was shown that HMGB1 exhibits enhanced proinflammatory activity by binding to cytokines, specifically IL-1β and TNF-α [29,30]. Therefore, we proposed that inflammation may be potentiated by a complex formation of HMGB1 with IL-1β and TNF-α, found to be elevated in the CSF of RR-MS patients [5,16], but our study could not detect an increase in any of these molecules. The lack of difference compared with control samples indicates that the described pathogenic mechanism is not important for MS at the disease onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Satoh et al . identified aberrant expression of apoptosis and DNA damage-regulating genes in MS PBMC, wheres Romme-Christianson and colleagues identified cytokine expression profiles in CSF and whole blood (WB) in RRMS patients [86,87]. Hecker et al .…”
Section: Part Ii: Discovery Of Novel (Non-imaging) Biomarkersmentioning
confidence: 99%
“…Furthermore, peripheral blood mononuclear cells (PBMCs) are being considered as an easily accessible and informative source of biological material in MS transcriptome studies (Achiron et al, 2004; Bomprezzi et al, 2003; Singh et al, 2007). In this line, it has been reported that the study linking peripheral and CSF immune responses were essential to understand the immunopathogenesis of MS (Christensen et al, 2012). …”
Section: Introductionmentioning
confidence: 99%